Research On TBI-2 Students' Perceptives On The Use Of Phonology-Based Intruction To Enhance English Speaking Fluency - Tanzila Bahar; Nur Ain Nun; Yani Lubis (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2023)
This research aimed to explore how students perceive the use of phonology-based instruction to enhance English speaking fluency. The study was done through the qualitative method using a Google form to collect the data. The results show that 40% of respondents responded with a neutral opinion, 20% of respondents agreed, 20% strongly agreed, 13.3% disagreed and 6.7% strongly disagreed. The results also show that most of the respondents agreed that understanding phonology is important in developing English-speaking skills. However, there is still a lack of confidence in speaking English with the use of phonology-based instruction. According to the results, it is evident that phonology-based instruction can assist in improving English speaking fluency. Suggestions were given in terms of having more resources to support using phonology-based instruction and having teachers assist learners in grasping the concept of phonology more easily.